A feasibility study of the combined school/public library in the Municipality of San Juan - Santos, Harriet R., II; Faderon, Rosalie B. (Quezon City Institute of Library Science, University of the Philippines Diliman, 2001)
The purpose of this study was to determine the feasibility of starting a combined school/public library in the municipality of San Juan. Specifically, the study aimed to answer the following questions: What are the reading needs of the constituents of the San Juan Municipality? Do they want/need a library? Is it feasible to establish a combined school/public library in San Juan? What would be the collection, staffing and services to be put up in the combined school/public library of San Juan? A questionnaire and an interview were utilized for this study.
Four factors were used to show the feasibility of the combined school/public library program. Users' need analysis showed that the San Juan community has a need for a combined library. The three other factors such as the technical, financial and organizational and management, show that there is little difference in establishing a combined school/public library and other library programs.
The researcher gave four recommendations for this study: 1) Planning of a combined school and public library should be done locally. 2) On hiring the appropriate librarian is a requirement. 3) The Department of Education, Culture and Sports (DECS) should consider this type of library to be adopted in all or in some parts of the Philippines. 4) Willingness to work of the concerned parties should be the most important factor in having a combined school and public library.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Public libraries -- Philippines -- San Juan; School libraries -- Philippines -- San Juan